Fitur Perangkat Ajar Kesehatan Dalam Website Sebagai Media Promosi Kesehatan Kemenkes Ri di Era Digital - Prasanti, Ditha; Seti Indriani, Sri (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2024)
The Ministry of Health of the Republic of Indonesia (Kemenkes RI) presents a new look as one of the menus on its website. This also answers the challenges of today's digital era in efforts to promote and educate various health programs. In this research, the author raises a new feature called “health teaching tools” which contains a variety of educational media for elementary, junior high, and high school children. This is very interesting to study from a health communication perspective. The purpose of this research is to find out the digital content contained in the health teaching tools feature of the Ministry of Health RI website; knowing the interactions that occur in the feature. The research method used is the virtual ethnography method. The development of information and communication technology has brought significant changes in the way information is delivered, including in the health sector. This article examines the features of health teaching tools available on the website of the Indonesian Ministry of Health. The results show that there are various educational and interactive features that can increase public awareness and knowledge about health issues. However, there are still challenges in terms of accessibility and utilization by all levels of society. This study recommends the development of more innovative and inclusive features to reach all segments of society in Indonesia.